Holistic approach to restore marine ecosystems: RENOVATE project - Marco Marcelli; Sergio Scanu; Daniele Piazzolla; Simone Bonamano; Alice Madonia; Giorgio Fersini; Viviana Piermattei; Mar Bosch-Belmar; Francesco Paolo Mancuso; Giulia Ceccherelli; Annalisa Falace; Paola Del Negro; et al. (Frontiers in Marine Science, 2026)
Mediterranean coastal ecosystems are increasingly threatened by multiple anthropogenic pressures and climate change. As a result, these impacts have caused the decline of key endemic habitats such as Posidonia oceanica meadows and coralligenous reefs. Due to the slow natural recovery of these habitats after degradation, restoration actions play a key role in accelerating ecosystem recovery, reestablishing ecological structure and functional processes, and preventing further biodiversity and ecosystem service loss. Given the frequent habitat fragmentation and high levels of endemism, effective restoration efforts require a multidisciplinary, ecosystem-based approach that integrates marine science, engineering, socioeconomics, and policy. This study describes the holistic approach adopted in the RENOVATE project, which established an integrated framework to address the combined impacts of climate change and human pressures on vulnerable ecosystems. The framework employs advanced observational technologies, field data, and numerical modeling within an adaptive management loop, enabling site-specific, evidence-based restoration planning and assessment of ecosystem services recovery. Additionally, the study reports results from the northern Tyrrhenian coast (Latium, Italy), where RENOVATE aims to protect EU priority habitats and species from human pressures and climate-related threats. Although project activities are still in early stages, results from active restoration in the northern Latium coast show initial establishment and survival at pilot sites, highlighting the framework’s potential to guide effective, replicable interventions in coastal ecosystems. Beyond the regional case study, the proposed framework contributes to global marine restoration efforts by providing a transferable methodology for the management of coastal ecosystems.

Antioxidant activity of methanol extract of Helichrysum foetidum Moench - Bruno Tirillini; Luigi Menghini; Lidia Leporini; Nadia Scanu; Stefania Marino; Giorgio Pintore (Natural Product Research, 2013)